Rcall: An R interface for MATLAB - Janine Egert; Clemens Kreutz (SoftwareX, 2023)
R and Matlab are two high-level scientific programming languages which are frequently applied in natural sciences like physics, mathematics and computational biology. New methods and applications are often implemented solely in R or solely in MATLAB. Here, we present the Rcall interface which provides users with access to the wide variety of methods programmed in R and in MATLAB. Rcall runs in MATLAB and provides direct access to methods and software packages implemented in R, accessible for example from Bioconductor or CRAN. The easy combination of MATLAB and R methods greatly extends the functionality of the MATLAB programming environment and makes Rcall well-suited for benchmarking implementations of the two programming languages. The MATLAB source code is available at https://github.com/kreutz-lab/Rcall. Rcall is supported on Linux, Unix-like, MS Windows and Mac OS X systems.